KUALITAS BIOLOGIS AIR KOLAM RENANG UMUM DI KOTA TANGERANG - Aminah Aminah; Makhabbah Jamilatun (Jurnal Ilmu dan Teknologi Kesehatan, 2017)
Various studies have shown that swimming pool mismanagement could serve as medium for water-borne diseases transmission. The research aimed to assess the biological quality of public swimming pool water in Tangerang city. One public swimming pool at the center of Tangerang city was assessed during November – December 2016 by adding two parameters to routine bacteriological indicators assessed by Tangerang city Heath Official in publicfacilities. Nine samples taken from three points in the swimming pool at three time periods, i.e. before, after, and during operational hours were analysed in the laboratory for detection and quantificaton of bacteriological indicators of swimming pool water, i.e. coliform, Escherichia coli, Staphylococcus, and Pseudomonas aeruginosa. Results showed that the number of total coliform and Escherichia coliof the public swimming pool exceeded WHO guidelines but not Peudomonas and Staphylococcus. Therefore,the disinfection, cleaning, and monitoring procedures need to be improved as well as increasing public swimming pool users education about the risk of potential transmissible diseases in public swimming pool.